ChemInform Abstract: 2‐(Trifluoromethyl)indoles via Pd(0)‐Catalyzed C(sp3)—H Functionalization of Trifluoroacetimidoyl Chlorides. Issue 34 (4th August 2016) - Pedroni, Julia; Cramer, Nicolai
Abstract: This complementary approach to trifluoromethylated indoles avoids the utilization of expensive electrophilic trifluoromethylating reagents.